Men can cook: Effectiveness of a men’s engagement intervention to change attitudes and behaviors in rural Ethiopia - Alderman, Harold; Gilligan, Daniel O.; Hidrobo, Melissa; Leight, Jessica; Mulford, Michael; Tambet, Heleene (Elsevier, 2025)
Graduation model interventions seek to address multiple barriers constraining households’ exit from poverty, however, few explicitly target restrictive gender norms. Using a randomized controlled trial design, combined with three rounds of data, we investigate the impacts on gender equitable attitudes and behaviors of a graduation program that seeks to address multiple constraints for those in poverty and improve restrictive gender norms in Ethiopia. We find that at 1-year follow-up all treatment arms lead to improvements in men’s gender equitable attitudes and their engagement in household domestic tasks as reported by both men and women; but at 3-year follow-up, impacts are only sustained in the treatment arms that introduced men’s engagement groups after the 1-year follow-up survey to further promote improvements in equitable gender norms.